Single Port Laparoscopic (SPL) Inguinal Hernia Repair in Girls - Muhammad Riaz-Ul-Haq, Shafiq-Ur-Rehman, Yasir Makki, Muhammad Anwar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Inguinal hernia in children is a very common surgical condition. Various techniques are being done for hernia repair in children. Single port needlescopic assisted hernia repair in girls is a time honoured technique with minimum complications and excellent Aim: To determine the outcome of single port needle assisted hernia repair in girls. Study design: Descriptive case series Place and duration of study: Department of Paediatric Surgery Sahiwal Teaching Hospital and Sahiwal Medical College Sahiwal between March 2021 and February 2022. Methodology: Twenty eight female patients from 3-13 years old with inguinal hernia underwent single port needlescopic assisted hernia repair. Follow up was done for three months to evaluate outcome with respect to recurrence, stitch abscess and cosmetic appearance. Results: Maximum patients between 7-10 years 12(42.85%). Fifty percent were right sided inguinal hernias. Four (14.28%) girls were developed complications. Two (7.14%) developed retroperitoneal intraoperative hematoma, 1(3.57%) stitch abscess and 1(3.57%) recurrence respectively. One patient with intraoperative hematoma was converted to open herniotomy. Stitch abscess was managed conservatively and recurrent hernia was repaired by open herniotomy. Conclusion: Single port laparoscopic needlescopic assisted hernia repair in girls is a simple and safe procedure with minimum complications and excellent cosmetic results. Keywords: Hernia, Inguinal, Girls, Single port, Needlescopic